Quinze anos de ecografia intravascular coronária em intervenção coronária percutânea em Portugal - Guerreiro, R (2019)
INTRODUCTION: Coronary intravascular ultrasound (IVUS) is increasingly important in catheterization laboratories due to its positive prognostic impact. This study aims to characterize the use of IVUS in percutaneous coronary intervention (PCI) in Portugal. METHODS: A retrospective observational study was performed based on the Portuguese Registry on Interventional Cardiology of the Portuguese Society of Cardiology. The clinical and angiographic profiles of patients who underwent PCI between 2002 and 2016, the percentage of IVUS use, and the coronary arteries assessed were characterized. RESULTS: A total of 118 706 PCIs were included, in which IVUS was used in 2266 (1.9%). Over time, use of IVUS changed from none in 2002 to generally increasing use from 2003 (0.1%) to 2016 (2.4%). The age of patients in whom coronary IVUS was used was similar to that of patients in whom IVUS was not used, but in the former group there were fewer male patients, and a higher prevalence of cardiovascular risk factors (hypertension, hypercholesterolemia and diabetes), previous myocardial infarction, previous PCI, multivessel coronary disease, C-type or bifurcated coronary lesions, and in-stent restenosis. IVUS was used in 54.8% of elective PCIs and in 19.15% of PCIs of the left main coronary artery. CONCLUSION: Coronary IVUS has been increasingly used in Portugal since 2003. It is used preferentially in elective PCIs, and in patients with higher cardiovascular risk, with more complex coronary lesions and lesions of the left main coronary artery.